Trichocera (Metatrichocera) gigantea Dahl 1967 ... - Petrašiūnas, Andrius; Podėnas, Sigitas (Zenodo, 2011)
Trichocera (Metatrichocera) gigantea (Dahl, 1967) Metatrichocera gigantea Dahl, 1967. Dahl, 1967b: 195. Trichocera (Metatrichocera) gigantea (Dahl, 1967). Dahl & Alexander, 1976: 14. Illustrated by Dahl, 1967b: figs. 15–19, 28–31. Material examined. MONGOLIA: 1 male, Hovsgol Aimag, Khankh Soum, Noyon river bank, N51.201528 E100.807278, altitude 1709 m, 8–15 August, 2005, Malaise trap, coll. O. Yadamsuren and S. Enkhtaivan, habitat: narrow valley with boggy forb-sedge meadow (Carex sp., Leymus chinensis, Potentillia sp.), vegetation coverage 70 percent, malaise trap at river edge. The species was known from Sweden (Dahl, 1967), Finland (Dahl, 1968) and Arctic tundra of Russia (Lantsov & Chernov, 1987). Occurrence of species in permafrost zone of Northern Mongolia was expected, despite disjunction with the rest of the distribution area. ... : Published as part of Petrašiūnas, Andrius & Podėnas, Sigitas, 2011, Notes on winter flies Trichoceridae (Diptera) of Mongolia with description of new species, pp. 61-68 in Zootaxa 3031 on page 62, DOI: 10.5281/zenodo.278712 ...